Addition of blood to a phycogenic bone substitute leads to increased in vivo vascularization. (11th September 2015) - Barbeck, Mike; Najman, Stevo; Stojanović, Sanja; Mitić, Žarko; Živković, Jelena M; Choukroun, Joseph; Kovačević, Predrag; Sader, Robert; James Kirkpatrick, C; Ghanaati, Shahram
Abstract: The present study aimed to analyze the effects of the addition of blood to the phycogenic bone substitute Algipore ® on the severity of in vivo tissue reaction. Initially, Fourier-transform infrared spectroscopy (FTIR) of the bone substitute was conducted to analyze its chemical composition. The subcutaneous implantation model in Balb/c mice was then applied for up to 30 d to analyze the tissue reactions on the basis of specialized histochemical, immunohistochemical, and histomorphometrical methods. The data of the FTIR analysis showed that the phycogenic bone substitute material is mainly composed of hydroxyapatite with some carbonate content. The in vivo analyses revealed that the addition of blood to Algipore ® had a major impact on both angiogenesis and vessel maturation. The higher vascularization seemed to be based on significantly higher numbers of multinucleated TRAP-positive cells. However, mostly macrophages and a relatively low number of multinucleated giant cells were involved in the tissue reaction to Algipore ® . The presented data show that the addition of blood to a bone substitute impacts the tissue reaction to it. In particular, the immune response and the vascularization were influenced, and these are believed to have a major impact on the regenerative potential of the process of bone tissue regeneration.